Managing the Neglected and the Residual Clubfeet with the New Operative Procedure (Hussain’s Procedure) – An Experience of Six-Month Fellowship - Lakhey, Rajesh Bahadur; Hussain, Afzal (Journal of Nobel Medical College, 2021)
Background: Pakistan Society for Rehabilitation of the Disabled Orthopedic Hospital is renowned for the correction of orthopedic deformities including foot and ankle deformities. Dr. Afzal Hussain, a consultant orthopedic surgeon in the hospital, pioneers in treatment of foot and ankle deformities and he has developed a new operative procedure for congenital clubfoot. Working with the surgeon for 6 months during the fellowship, management of the neglected and the residual congenital clubfeet with the new operative procedure   and their follow-ups were assisted by the first author.Materials and Methods: Operative procedure of the neglected and the residual congenital clubfeet, which were performed with the new operative procedure by Dr. Hussain, were assisted by the first author and a minimum of 5 years follow up was done by the senior author (Afzal Hussain). Cumming’s modification of Laavag and Ponseti score was applied for the calculation of the results at the follow-ups.Results: During the follow-ups of 11 cases of neglected congenital clubfeet and 9 cases of residual clubfeet (operated earlier with posteromedial release) which had been operated by the new operative procedure, Cumming’s modification of Laavag and Ponseti scores of the operated clubfeet were calculated and the results were found to be excellent.Conclusion: Early results of the new operative procedure by Dr. Afzal Hussain for congenital clubfoot in the neglected and the residual congenital clubfeet were found to be excellent.